CANTIK ALA REMAJA DALAM NOVEL-NOVEL TEENLITE - Lilik Setijowati; Khrsitianto Khristianto (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2008)
Young female writers shocked the literary field of Indonesia by publishing their works in their way: light, unburdened, and fresh. Their language choice is easily understandable: the novels were written in colloquial style. The books were sold well. It did refresh our literary world. The teenagers, at least, have more alternatives to read something composed by their peers. Through their pens, our teens share their views on reality in their very style.                        One of outstanding concepts evoked in their writing is the formulation of “ beauty”. This paper took four novels, My Friends-My Dream, Ramalan Fudus Ororpus, Kana di Negeri Kiwi, dan Summer Triangle, to discover the teen’s perspective concerning beauty. The concept is internalized in their mind through the discourses developed in their social background and through the media. They select those discourses, and take one they believe in it.                    They analysis shows that their concept of beauty is not so different from the general one or patriarchal beauty. However, they insist that being beauty does not necessarily mean to be happy, as it was obviously declared in Kana di Negeri Kiwi. The beauty is : tall, white, black and straight hair, and well-shaped  body. This is just a result of the dominance of patriarchy, standing in the same position of capitalism to whom the main stream media are belonged. The media holder is the only one dictating what’s to be “ beauty.”